Challenges of Fiscal Policy in Emerging and Developing Economies - Huidrom, Raju; Kose, M. Ayhan; Ohnsorge, Franziska L. (Taylor and Francis, 2018)
This article presents a systematic analysis of the availability and use of fiscal space in emerging and developing economies. We report two major results. First, emerging and developing economies built fiscal space in the run-up to the Great Recession of 2008–2009, which was then used for stimulus. Since then, fiscal space has shrunk and remains narrow as these economies have taken advantage of historically low interest rates. Second, fiscal policy in emerging and developing economies has become countercyclical (or less procyclical), i.e., “graduated,” since the 1980s, as most clearly demonstrated during the Great Recession. The move towards graduation is most pronounced for those economies with greater fiscal space, which suggests that fiscal space matters for a government’s ability to implement countercyclical fiscal policy.